Fostering a Green Generation: Associations between Core Values and Pro-Environmental Behavioral Intentions among College Students - Arina Shabrina; Aulia Zakiyah Almardiyah; Taufan Dwirajasa; Shafa Hasna Zahidah (Jurnal Ecopsy, 2026)
Human activities exacerbate environmental degradation and climate change. Pro-environmental behavior can help mitigate these effects, and intention is a key predictor of such behavior. This study examined the associations between basic values and intentions to engage in pro-environmental behavior among university students. An online survey was conducted with 127 students using the Indonesian version of the Portrait Values Questionnaire (PVQ-40) and a pro-environmental behavior intention scale. Universalism and self-direction were weakly and positively correlated with pro-environmental intentions, whereas hedonism and power were weakly and negatively correlated. These findings indicate that basic values are related to pro-environmental intentions, although only selected values showed significant associations. In particular, values within self-transcendence and openness to change were associated with pro-environmental intentions. Interventions that seek to strengthen pro-environmental behavior should therefore foster concern for others, concern for nature, and openness to new ideas.